Company Profile Website Development Using Prototyping Method - Nicky adi putra; Yefta Christian (Cakrawala Repositori IMWI, 2023)
Fabrication is a field that is much needed in the industry now due to the increasing industrial sector, one of the companies working in this sector is PT Cipta Indah Bangun Pertiwi. Even though it has been operating for more than 1 decade, it still does not have a website that helps them to reach more customers. For this reason, the author wants to help in achieving sales targets for partners by forming a website that is created as a medium to show the company profile of Cipta Indah Bangun Pertiwi that consists of, detailed information related to company history, contacts, addresses and services provided. This website is designed using couple of programming languages, such as Javascript, and HTML5. This research is expected to help PT CIBP with this website, making it easier for readers to know the background profile and can increase potential customers.